Pengaruh Biaya Produksi Dan Harga Jual Terhadap Laba Penjualan Pada PT Shimano Batam - Baru Harahap (JURNAL AKUNTANSI BARELANG, 2019)
The purpose of this research is to determine the effect of production costs and selling prices on increasing sales profits at PT Shimano Batam. The sample used in this study is financial statements: (1). PT Shimano Batam financial statements before the period 2013 - 2017; (2). The financial statements of PT Shimano Batam that were listed during the period 2013 - 2017; and (3). The financial statements have been audited as of December 31, 2013 - 2017. The results of this study have a significant effect on production costs and selling prices on increasing sales profits at PT Shimano Batam with significant values of 0,000 and 0,000 <0,05, respectively. While simultaneous production costs and selling prices have a significant effect on increasing sales profits at PT Shimano Batam with a significant value of 0,000 <0,05.